Olmesartan inhibits cultured rat aortic smooth muscle cell death induced by cyclic mechanical stretch through the inhibition of the c-Jun N-terminal kinase and p38 signaling pathways - Satoyasu Ito; Kentaro Ozawa; Jing Zhao; Yoji Kyotani; Kosuke Nagayama; Masanori Yoshizumi (Elsevier, 2015)
Acute aortic dissection (AAD) is a life-threating disease; however, there is almost no effective pharmacotherapy for it. An increase in c-Jun N-terminal kinase (JNK) phosphorylation and smooth muscle cell (SMC) apoptosis is observed tissues in patients with AAD. Therefore, we hypothesized that an acute rise in blood pressure leads to SMC death through phosphorylation of JNK or p38, which may cause AAD. We investigated the influence of cyclic mechanical stretch, which mimics an acute increase in blood pressure, on cultured rat aortic SMCs (RASMCs) and examined the changes in JNK and p38 phosphorylation. Further, we investigated the effect of olmesartan, an angiotensin II receptor blocker, on stretch-induced RASMC death. We found that mechanical stretch-induced RASMC death in a time-dependent manner, which correlated with the phosphorylation of JNK and p38. Olmesartan inhibited RASMC death and the phosphorylation of JNK and p38. JNK and p38 inhibitors reversed stretch-induced RASMC death. These results suggest that acute mechanical stretch causes JNK and p38 phosphorylation, which may result in SMC death leading to aortic dissection. Olmesartan may be used for pharmacotherapy to prevent aortic dissection, independent of its blood pressure-lowering effect, through its inhibition of JNK and p38 phosphorylation.